2018
DOI: 10.1186/s12913-018-3497-8
|View full text |Cite
|
Sign up to set email alerts
|

Entertaining accurate treatment expectations while suffering from chronic pain: an exploration of treatment expectations and the relationship with patient- provider communication

Abstract: BackgroundAccurate patient expectations are important to optimise treatment success, especially for complex conditions such as chronic pain. Communication may be the key to managing patient expectations. This study aimed to explore whether health care provider communication influences patient expectations and which communication aspects are most important.MethodsWe conducted secondary analyses on data that had been collected between September and November 2012. 2603 patients suffering from chronic pain were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Clinically, these findings highlight the importance of assessing and addressing treatment expectations at the start of IIPT. Results indicated that higher levels of caregiver expectations, specifically “extremely high” expectations, were associated with more youth pain-related disability and distress at both IIPT admission and discharge, Thus, ensuring that patients and their caregivers adopt realistic expectations of treatment may be especially important for medically complex chronic conditions such as pediatric chronic pain 38. The initial evaluation may be an opportune time for clinicians to provide psychoeducation that adjusts treatment expectations so that they are more reasonable and moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, these findings highlight the importance of assessing and addressing treatment expectations at the start of IIPT. Results indicated that higher levels of caregiver expectations, specifically “extremely high” expectations, were associated with more youth pain-related disability and distress at both IIPT admission and discharge, Thus, ensuring that patients and their caregivers adopt realistic expectations of treatment may be especially important for medically complex chronic conditions such as pediatric chronic pain 38. The initial evaluation may be an opportune time for clinicians to provide psychoeducation that adjusts treatment expectations so that they are more reasonable and moderate.…”
Section: Discussionmentioning
confidence: 99%
“…The current study extends understanding of the mechanisms through which contextual factors may impact patient health outcomes. Earlier studies have investigated pathways among smaller numbers of contextual variables and suggested, for example, that self-efficacy mediates the impact on osteoarthritis pain of practitioners communicating positive expectancies, 35 affective aspects of the therapeutic relationship may shape Open access patient expectancies in chronic pain, 70 and expectancies might impact pain via reduced catastrophising in chronic back pain. 33 The current results further suggest contextual factors reduce back-related disability in part by enhancing patient self-efficacy for coping with pain, reducing the perceived threat of pain and reducing psychosocial distress.…”
Section: Discussionmentioning
confidence: 99%
“…We most probably failed to explain to our patients more explicitly the difference between expectation and desire for pain relief. It seems advisable therefore to be more careful and clearly communicate when asking about patient expectations ( 14 ).…”
Section: Discussionmentioning
confidence: 99%